Interdisciplinary Integration of Sustainable Development Goals in Secondary Education - Rena Alasgarova; Eltaj Maharramova (Journal of Education for Sustainable Development Studies, 2026)
This qualitative study examines the role of teacher collaboration in integrating the Sustainable Development Goals (SDGs) into interdisciplinary secondary education in Azerbaijan. A total of 157 educators and school leaders from 20 schools participated in in-depth interviews, providing insights into their knowledge of SDGs, collaboration practices, and perceived institutional support. The study identifies that while educators demonstrate a general awareness of the importance of sustainability, their initial understanding of the SDGs is often vague or incomplete. Once clarified, participants recognized that many of their existing practices already align with SDG competencies, albeit unintentionally. The findings highlight several critical barriers to effective SDG collaboration, including heavy emphasis on exam-driven instruction, limited practical training, inconsistent communication, and scarcity of instructional resources aligned with local language and classroom needs. The Ministry of Education’s requirement for schools to prepare sustainability-themed action plans has increased visibility of SDG-related initiatives; however, teacher engagement in planning and interdisciplinary collaboration remains limited due to administrative centralization of responsibilities. The study proposes a comprehensive teacher development framework emphasizing SDG literacy enhancement, structured collaboration, and interdisciplinary pedagogical innovation. Practical implications include the need for systematic professional development, distributed leadership models, and deeper community participation in sustainability initiatives. The findings further contribute to theoretical perspectives on sustainable education by highlighting how shared vision and institutional support facilitate interdisciplinary teaching practices. This research advances understanding of the contextual challenges and opportunities for SDG education in post-Soviet educational systems and underscores the importance of empowering teachers as proactive change agents in promoting sustainability across the curriculum.